Assessment of the Skin and Heart Tissue Damage Following Inhalation of Carbon Nanotubes in Wistar Rats Using Isolated Mitochondria: Carbon nanotubes induced skin and heart tissue damage - Samiei, Fatemeh; Dousti, Faezeh; Seydi, Enayatollah; Hayati, Ali; H. Shirazi, Farshad; Pourahmad, Jalal (Iranian Journal of Pharmaceutical Sciences, 2021)
The unique properties of carbon nanotubes (CNTs) have led to their use in various fields. But, the toxicity of CNTs has been reported in biological and environmental systems. The aim of this research is to study the effect of multi-wall carbon nanotubes (MWCNTs) through inhalation chamber on the mitochondrial damage and oxidative stress using the mitochondria obtained from the skin and heart. Rats were exposed to 5 mg/m3 of MWCNTs (10 nm) aerosol for 5 hours /day, 5 days/week for 2 weeks in a whole-body exposure chamber. After 2-weeks exposure, Heart and skin mitochondria were evaluated for evaluation of toxicity parameters. The results showed that nanoparticles significantly decreased mitochondrial succinate dehydrogenase (SDH) activity and increased the level of reactive oxygen species (ROS), collapse in mitochondria membrane potential (MMP), swelling in mitochondria, and cytochrome release. In conclusion, we suggested that 5 mg/m3 of MWCNTs (10 nm) induce ROS mediated cytotoxicity by directly targeting mitochondria in both skin and heart tissue.